Nickel (II)-citric acid complex formation in aqueous solution : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Chemistry at Massey University - Liddle, John Raymond (Massey University, 1979)
Titrimetric analysis of solutions of nickel(II) chloride and citric acid, H 3 L, has led to the characterization of four complexes in the acidic pH range NiL - , NiHL, NiH 2 L + , and Nil 4- 2 . Equilibrium constants for the formation of these complexes are reported. Results from a visible spectrophotometric study are analysed in terms of these four complexes. The stability and possible structures of the complexes are discussed and compared with other nickel-carboxylic acid complexes.
Keywords: Nickel; Nickel compounds; Citric acid; Citric acid compounds